2016
DOI: 10.1188/16.cjon.289-297
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Administered Sleep Intervention for Patients With Cancer Experiencing Insomnia

Abstract: Adherence to the sleep intervention was high (75%), and significant improvement was found in global sleep quality (p < 0.0001) regardless of level of adherence. Sleep onset latency (p = 0.0005), sleep duration (p = 0.0016), and sleep quality (p < 0.0001) were significantly improved. Age was significantly correlated with sleep quality (p = 0.0094), with older participants reporting greater benefit from the intervention. Participants reported that the intervention was easy to learn and implement and that it "cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Younger age was identified as a predictor of wake time variability in one study 40 , but not in another 10 ; older age was a predictor of bedtime and rise time variability 62 , although another study did not find a significant relationship between age and adherence 48 . Post-secondary education and employment status was not related to self-reported adherence 16,40 . Having a bed partner or pet was positively related to adherence to stimulus control 30 .…”
Section: Demographicsmentioning
confidence: 79%
See 4 more Smart Citations
“…Younger age was identified as a predictor of wake time variability in one study 40 , but not in another 10 ; older age was a predictor of bedtime and rise time variability 62 , although another study did not find a significant relationship between age and adherence 48 . Post-secondary education and employment status was not related to self-reported adherence 16,40 . Having a bed partner or pet was positively related to adherence to stimulus control 30 .…”
Section: Demographicsmentioning
confidence: 79%
“…There were conflicting findings regarding subjective adherence measures. While some found that self-reported 16,44 adherence was not related to treatment outcomes, in two studies self-reported frequency of using treatment components was significantly related to lower ISI scores post-treatment, for overall CBT-I use (r=0.53 20 ) and adherence specifically for cognitive (r =−0.34 58 ) and behavioural components (r=−0.27 58 ).…”
Section: Subjective Datamentioning
confidence: 89%
See 3 more Smart Citations